Muscle Strength Deficit though Intact Proprioception after Lateral Ankle Sprain without Persistent Instability - Madkhali, Adel M.; Nuhmani, Shibili (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2021)
Background Lateral ankle sprain is one of the most common injuries in competitive sports. Previous studies which investigated muscle strength and proprioception (joint position sense) focused on subjects who sustained ankle sprain with instability. It is also important to investigate strength deficits and proprioception in subjects with a history of ankle sprain without instability. Therefore the aim of the study is to investigate proprioception and muscle strength deficits in athletes with lateral ankle sprain.Methods Twenty-four male athletes with a history of lateral ankle sprain and 24 age-matched controls (mean age of 22.42±4.13 years, mean height of 173±5.73 cm, and mean weight of 71.20±7.55 Kg) participated in this cross-sectional study. Peak torque and peak torque ratio at speeds of 30 and 120°/s for concentric and eccentric ankle inversion/eversion were evaluated using an isokinetic dynamometer. The joint position sense of the ankle joint was evaluated using an active angle reproduction test.Result Peak torque produced was significantly less in subjects with history of ankle sprain in concentric inversion 30°/s(t(47)=4.11; p=0.000, Cohen’s d=1.29), concentric inversion 120°/s (t(47)=3.01; p=0.006, Cohen’s d=1.13), concentric eversion 30°/s (t(47)=3.85; p=0.001, Cohen’s d=1.24) and concentric eversion 120°/s (t(47)=3.15; p=0.005, Cohen’s d=1.09). At the same time there was no significant difference observed in eccentric eversion peak torque in both speed (eccentric eversion 30°/s p=0.079; eccentric eversion 120°/s p=0.867) between experimental and control group. No significant difference was found in the joint position sense in the maximal active inversion −5° position (p=0.312) and the 15° inversion position (P=0.386) between both group.Conclusion The study’s results reported a significantly less peak torque of invertors and evertors during concentric movements in athletes with history of ankle sprain. At the same time, no significant difference reported in the evertor/invertor peak torque ratio, and active joint position sense between the 2 groups.
Keywords: isokinetic strength testing; rehabilitation; rehabilitation outcome